Fostering Environmental Health Literacy in Contaminated Sites: National and Local Experience in Italy From a Public Health and Equity Perspective - Marsili, Daniela; Pasetto, Roberto; Iavarone, Ivano; Fazzo, Lucia; Zona, Amerigo; Comba, Pietro (Frontiers in Communication, 2021)
The present paper deals with Environmental Health Literacy (EHL) in contaminated sites. The Italian national epidemiological surveillance system of population resident in contaminated sites, including vulnerable subgroups, and the local epidemiological studies and communication initiatives implemented in specific sites are considered. The Italian experience in contaminated sites corroborates the importance of EHL as a key component of community capacity to participate in mitigating environmental health risks. Effective access to evidence-based information on environmental health risk is the basis for improving awareness of local institutional and social actors. The proactive involvement of stakeholders in preventive actions and the adoption of shared practices reflect the progressive increase of their EHL. Bidirectional communication relying on participative approaches, collaborative national-local initiatives and dialogue with the communities is an effective tool for increasing EHL at each site. This enhances the community capacity to use the acquired knowledge in promoting prevention actions. Consideration of socioeconomic fragilities and vulnerable groups in well-designed EHL practices contributes to prevent adverse health effects induced by specific environmental exposures and to promote Environmental Justice at local level.